PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), CORPORATE IMAGE, DAN KEPUTUSAN NASABAH TERHADAP LOYALITAS NASABAH - Ahmad Faqihudin; Meinarni Asnawi; Bill J.C Pangayow (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2020)
This study aims to examine the influence of corporate social responsibility (CSR) implementation, corporate image, and customer satisfaction, on customer loyalty. Variables independent were used inthis study namely Corporate Social Responsibility (CSR), corporate image, and customer satisfaction., as well as one dependent variable of customer loyalty. Customers of PT Bank Rakyat Indonesia Jayapura are used as the population in this study. The convenience sampling with a sample of 30 respondents is the technique of sampling method in thisstudy. This study uses a double linear regression analysis to analyses data. The analysis tool used is SPSS version 23. The results of this research demonstrate the implementation of Corporate Social Responsibility (CSR) has positively and significantly affects customer loyalty. Corporate Image has a positive and significant impact on customer loyalty. And customer satisfaction has a positive but does nosignificant impact on customer loyalty.